Burden of hospitalizations over time with invasive aspergillosis in the United States, 2004-2013 - Marya D. Zilberberg; Rachel Harrington; James R. Spalding; Andrew F. Shorr (BMC, 2019)
Abstract Background Using aggregated data available on the interactive website from the Agency for Healthcare Research and Quality's Healthcare Cost and Utilization Project Network (HCUPnet), we examined the annual volume of invasive aspergillosis (IA)-related hospitalizations in the US. Methods This was a population study. Age-adjusted volumes were derived through population incidence calculated using year-specific censal and intercensal US population estimates available from the US Census Bureau. We additionally examined IA as the principal diagnosis and its associated outcomes in patients with ICD-9-CM codes 117.3, 117.9 and 484.6. Results The age-adjusted number of annual hospitalizations with IA grew from 35,968 cases in 2004 to 51,870 in 2013, a 44.2% overall increase, 4.4% per annum. Regionally, the South contributed the plurality of the cases (40%), and the Northeast the fewest (17%). While IA as principal diagnosis dropped, from 14.4 to 9.3%, mortality rose from 10 to 12%. Despite mean hospital length of stay decreasing from 13.3 (standard error [SE] 0.07) to 11.5 (SE 0.6) days, the corresponding mean hospital charges rose from $71,164 (SE $5248) to $123,005 (SE $9738). The aggregate US inflation-adjusted hospital charges for IA principal diagnosis rose from $436,074,445 in 2004 to $592,358,369 in 2013. Conclusions Given the substantial volume and rate of growth in IA-related hospitalizations in the US between 2004 and 2013, an increase in mortality and high costs, IA may represent an attractive target for intensive preventive efforts.